The impact of the euro on equity markets: a country and sector decomposition - Lorenzo Cappiello; Arjan Kadareja; Simone Manganelli (European Central Bank (ECB), 2008)
This paper investigates whether comovements between euro area equity returns at national and industry level have changed after the introduction of the euro. By adopting a regression quantile-based methodology, we find that after 1999 the degree of comovements among euro area national equity markets has augmented. By explicitly controlling for the impact of global factors, we show that this result cannot be explained away by recent world-wide trends. A more refined analysis based on an industry breakdown suggests that the increase in national index comovements is mainly driven by financial, industrials and consumer services sectors.
Keywords: F36; G15; C22; 330; conditional comovements; euro; National and industry equity returns; regression quantiles; Eigenkapital; Kapitaleinkommen; Finanzmarkt; Euro; Eurozone; EU-Staaten; Japan; USA